PELATIHAN KOMUNIKASI UNTUK MENINGKATKAN PENGETAHUAN MEMBERIKAN FEEDBACK PEGAWAI PANTI DINAS SOSIAL DIY - syahrizal, syahrizal (Psikoislamedia: Jurnal Psikologi, 2016)
This research aims to know the influence of communication training to enhance the knowledge of giving feedback on employees of the Government institution which is X. The current condition of the organization experienced a low ability to give feedback to a subordinate supervisor. The subject of this research as many as 13 people with characteristics of the subject are the employees who occupy positions as supervisor or leader of the condition have a subordinate in the subject work. Type of this research is the research design eksprimen one group pretest – posttest design using one group of participants who were given a treat or interventions with data analysis using t-test (t-test) paired simple test to see whether or not there is a difference between score gains pre-and post test-test on the subject of research. The results of this research show that there are influences of communication training to increase knowledge, give feedback from results of pre test post test with the value t =-4.234and significance of 0,001 (p